High-fat feeding impairs nutrient sensing and gut brain integration in the caudomedial nucleus of the solitary tract in mice. - Althea R Cavanaugh; Gary J Schwartz; Clémence Blouet (PLoS ONE, 2015)
Hyperphagic obesity is characterized in part by a specific increase in meal size that contributes to increased daily energy intake, but the mechanisms underlying impaired activity of meal size regulatory circuits, particularly those converging at the caudomedial nucleus of the solitary tract in the hindbrain (cmNTS), remain poorly understood. In this paper, we assessed the consequences of high-fat (HF) feeding and diet-induced obesity (DIO) on cmNTS nutrient sensing and metabolic integration in the control of meal size. Mice maintained on a standard chow diet, low-fat (LF) diet or HF diet for 2 weeks or 6 months were implanted with a bilateral brain cannula targeting the cmNTS. Feeding behavior was assessed using behavioral chambers and meal-pattern analysis following cmNTS L-leucine injections alone or together with ip CCK. Molecular mechanisms implicated in the feeding responses were assessed using western blot, immunofluorescence and pharmacological inhibition of the amino acid sensing mTORC1 pathway (mammalian target of rapamycin complex 1). We found that HF feeding blunts the anorectic consequences of cmNTS L-leucine administration. Increased baseline activity of the L-leucine sensor P70 S6 kinase 1 and impaired L-leucine-induced activation of this pathway in the cmNTS of HF-fed mice indicate that HF feeding is associated with an impairment in cmNTS mTOR nutritional and hormonal sensing. Interestingly, the acute orexigenic effect of the mTORC1 inhibitor rapamycin was preserved in HF-fed mice, supporting the assertion that HF-induced increase in baseline cmNTS mTORC1 activity underlies the defect in L-leucine sensing. Last, the synergistic feeding-suppressive effect of CCK and cmNTS L-leucine was abrogated in DIO mice. These results indicate that HF feeding leads to an impairment in cmNTS nutrient sensing and metabolic integration in the regulation of meal size.